On new traveling wave solutions of potential KdV and (3+1)-dimensional Burgers equations - Tchiera, Fairouz; Inan, Ibrahim E.; Ugurlu, Yavuz; İnç, Mustafa; Baleanu, Dumitru (Int Scientific Research Publications, 2016)
This paper acquires soliton solutions of the potential KdV (PKdV) equation and the (3+1)-dimensional Burgers equation (BE) by the two variables (G'/G, 1/G) expansion method (EM). Obtained soliton solutions are designated in terms of kink, bell-shaped solitary wave, periodic and singular periodic wave solutions. These solutions may be useful and desirable to explain some nonlinear physical phenomena. (C) 2016 All rights reserved.
Keywords: (G'/G, 1/G)-EM; the PKdV equation; the (3+1)-dimensional BE; hyperbolic solution; periodic solution; rational solution